2019
DOI: 10.1007/s00038-019-01319-9
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to cervical cancer screening in Guatemala: a quantitative analysis using data from the Guatemala Demographic and Health Surveys

Abstract: Objectives Examine the association between commonly reported barriers to health care, including discordant spoken languages between patients and providers, and reported previous cervical cancer screening. Methods Data from the nationally representative Guatemala National Maternal and Child Health Survey from the Demographic and Health Surveys Program were used to explore associations between barriers and screening rates nationwide and in high-risk populations, such as rural and indigenous communities. Negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
(35 reference statements)
3
13
0
1
Order By: Relevance
“…Our finding that pelvic examination is a barrier to screening corroborates previous reports from Minnesota [26], Guatemala [27], China [28] and Bangladesh [29]. In a qualitative study in Minnesota [26], pelvic examination was perceived as invasive and the use of speculum was considered problematic.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding that pelvic examination is a barrier to screening corroborates previous reports from Minnesota [26], Guatemala [27], China [28] and Bangladesh [29]. In a qualitative study in Minnesota [26], pelvic examination was perceived as invasive and the use of speculum was considered problematic.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to sociodemographic variables such as ethnicity, wealth, and education, analyses of DHS data have also highlighted the associations between several sexual health variables and cervical cancer screening, such as positive associations with prior history of STI and number of lifetime sexual partners. 4 Our analysis here confirms these findings for cervical cancer screening, but a similar pattern was not seen for retention in care after a positive cancer screen (Tables 1 and 4). We also find, for the first time in Guatemala, strong associations between contraceptive use and cervical cancer screening and care (Table 4).…”
Section: Discussionsupporting
confidence: 86%
“…A study in Latin American indigenous women [ 33 ] showed a higher risk of death from cervical cancer, which could be explained by the lower detection rate of early-stage cervical cancer and barriers to access treatment [ 10 , 33 35 ]. In addition, the socioeconomic disparities, lack of access to health care services, and low education in the rainforest region [ 36 ], have and continue to create a setting with a lack of knowledge, and poor education on cancer prevention, resulting in poor adherence to treatment and even rejection of screening [ 34 , 35 , 37 ]. These factors compromise the overall population health and prevent further reductions of mortality rates.…”
Section: Discussionmentioning
confidence: 99%